Comparison of single versus multiple doses of antibiotic prophylaxis in reducing post-elective Caesarean section infectious morbidity - Shakya, A; Sharma, J (Kathmandu University Medical Journal, 2010)
Background: Puerperal sepsis is frequently in Caesarean section. Antibiotic prophylaxis may have significant impact in reduction of infections and thus the need to study its role in sepsis prevention systematically. Objective: The aim of this study is to compare the efficacy of single dose versus multiple doses of a first generation cephalosporin (with Metronidazole), to reduce postoperative infectious morbidity in elective caesarean section. Materials and methods: It was prospective clinical trial of hundred women undergoing elective caesarean section who received either a single prophylactic dose of Cefazolin with Metronidazole post-cord clamping, or multiple postoperative doses of antibiotics based on the standard protocol of the hospital. Duration of the study was seven months and twentytwo days (11th November 2004 to 30th June 2005).Women were compared on the basis of development of postoperative febrile morbidity, endometritis, urinary tract infection, wound infection and other infections. Results: There were no significant differences among the patients in single and multiple dose groups in terms of their age distribution, gravida, period of gestation, smoking status, body mass index, indications for elective caesarean section or operation characteristics. There were 4% and 6% febrile morbidity, 2 (4%) and 0 (0%) urinary tract infection, in the single dose and multiple dose groups respectively. But none of the differences were statistically significant. Conclusion: A single prophylactic dose of Cefazolin plus Metronidazole given post-umbilical cord clamping gives as much protection as multiple postoperative doses of Cefazolin/Cefalexin plus Metronidazole in preventing postoperative infectious morbidity in elective caesarean section. Key words: Antibiotic prophylaxis; Caesarean section DOI: 10.3126/kumj.v8i2.3554 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 179-184